ANALISIS REDAMAN GETARAN PADA LANTAI TANGGA EKSISTING - Tarigan, Valentana Ardian; Panggabean, Immanuel Panusunan Tua (JUITECH: Jurnal Ilmiah Fakultas Teknik Universitas Quality, 2024)
Vibrations in certain building floor plate systems are excitations that arise from rhythmic human activities such as running, dancing and aerobic movements. The term “frequency content” refers to the number of modes across the floor system frequencies. The first natural frequency (fn), also referred to as the fundamental natural frequency, is used for floor vibrations for design purposes. In terms of fundamental natural frequencies, humans are more sensitive to low frequency vibrations than high frequencies. In response to floor vibrations, the human sensitive range is usually between 4 and 8 HZ. Analysis found that the stair floor plate structure with D10-150 floor reinforcement could withstand the design load. The cause of very pronounced vibrations on the stairs is caused by the natural vibration frequency on the stair plate < 8Hz. The selection of reinforcement for the stair floor plate is carried out in the middle of the floor plate span. After recalculating, the additional stiffness of the floor plate produces a vibration frequency of > 8Hz, so that the vibrations are no longer disturbing.